2006
DOI: 10.1093/hmg/ddi474
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation dependent allelic expression imbalance of BAPX1 in patients with the oculo-auriculo-vertebral spectrum

Abstract: The oculo-auriculo-vertebral spectrum (OAVS) (OMIM % 164210) is a common developmental disorder characterized by hemifacial microsomia, epibulbar tumours, ear malformation and vertebral anomalies. Although rare familial cases suggest that OAVS has a genetic basis, no genetic defect has been identified so far. In a patient with OAVS and a chromosomal translocation t(4;8) we have found that the chromosome 4 breakpoint is 76.4 kb distal to the BAPX1 gene, which plays an essential role in craniofacial development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 38 publications
2
52
0
3
Order By: Relevance
“…6 The heterogeneity of this condition has been further supported by the observation that epigenetic deregulation is associated with the occurrence of OAVS. 16 Although we observed three positive regions after we have analyzed all the members of F2, an LOD score of 3.0 was only observed with markers of chromosome 1. The LOD score of 3.01 observed with the marker D1S252 is the maximum possible LOD-score value that can be obtained in F2, assuming full penetrance.…”
Section: -15mentioning
confidence: 75%
“…6 The heterogeneity of this condition has been further supported by the observation that epigenetic deregulation is associated with the occurrence of OAVS. 16 Although we observed three positive regions after we have analyzed all the members of F2, an LOD score of 3.0 was only observed with markers of chromosome 1. The LOD score of 3.01 observed with the marker D1S252 is the maximum possible LOD-score value that can be obtained in F2, assuming full penetrance.…”
Section: -15mentioning
confidence: 75%
“…Therefore, studies of additional families are of importance to the identification of the loci involved. Fischer et al (2006) found abnormal BAPX1 expression in a significant number of OAVS patients and suggested that epigenetic disregulation of BAPX1 might play a role in the etiology of OAVS. In addition, a few patients showing clinical overlap with OAVS had mutations in sal-like 1 (SALL1) (Kohlhase et al 1999;Keegan et al 2001;Kosaki et al 2007) or Treacher Collins-Franceschetti syndrome 1 (TCOF1) (Su et al 2007), the genes responsible for most cases of Townes-Brocks syndrome [OMIM 107480] and Treacher Collins syndrome [OMIM 154500], respectively, which are also associated with first and second branchial arch anomalies.…”
mentioning
confidence: 97%
“…Therefore it is possible that in our patient multiple gene mutations possibly contiguous may have caused the OAVS, via malregutation of NCC development or migration, or via abnormal integration of NCC with mesodermal structures present in branchial arches and may have caused precocious puberty via hypothalamic-pituitary axis functional malregulation. Other studies have suggested a role of the Goosecoid gene (in chromosome 14q32) in hemifacial microsomia development 42 and of BAPXI gene 43 . In OAVS development further studies could indicate the abnormal genetic ground present in our patient, but NCC pathology seems to play a major role in OAVS.…”
Section: Discussionmentioning
confidence: 96%